2011
DOI: 10.1097/gim.0b013e318204cfed
|View full text |Cite
|
Sign up to set email alerts
|

Family communication matters: The impact of telling relatives about unclassified variants and uninformative DNA-test results

Abstract: Background: Unclassified variant and uninformative BRCA1/2 results are not only relevant for probands to whom results are disclosed but also for untested relatives. Previous studies have seldomly included relatives and have not explained how their lives were influenced by these results. We explored the family communication timeline of genetic counseling: (1) genetic counselors communicate the relatives' cancer risk, (2) probands perceive this risk and (3) communicate this to relatives; (4) relatives perceive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Rather than enhancing the content of the information given, genetic counseling strategies that assess personal and familial barriers to communication may provide more targeted support and may facilitate more open sharing within the family. In line with other studies showing the importance of the extent of the communication process on the impact genetic testing information has on relatives [44], our next paper will examine those factors which are associated with actual understanding of the test results by the informed relatives.…”
Section: Discussionmentioning
confidence: 89%
“…Rather than enhancing the content of the information given, genetic counseling strategies that assess personal and familial barriers to communication may provide more targeted support and may facilitate more open sharing within the family. In line with other studies showing the importance of the extent of the communication process on the impact genetic testing information has on relatives [44], our next paper will examine those factors which are associated with actual understanding of the test results by the informed relatives.…”
Section: Discussionmentioning
confidence: 89%
“…The mean number of information statements communicated to patients was 21 (range [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Participantsmentioning
confidence: 99%
“…More recently, a Dutch study found that patients' recall of information about BRCA1/2 genetic test results was similar to the information provided during genetic counselling, but there were few similarities between the information actually communicated to the patient and the information recalled by their relatives. 17 The authors concluded that the information was reinterpreted at each stage of the information transfer, highlighting problems with the accuracy of information communicated to relatives by patients.…”
Section: Introductionmentioning
confidence: 99%
“…These quality of life and survivorship issues in conjunction with the difficulty some patients may have to accurately recall their test results 149151 underscore the importance of pre- and posttest genetic counseling that is provided by a knowledgeable genetics professional. In addition to expertise in cancer risk assessment and medical management of individuals with hereditary cancer predisposition, these individuals are also trained to identify potential psychosocial and educational needs of patients.…”
Section: Quality Of Life and Survivorshipmentioning
confidence: 99%